Recognition and characterization of small-scale sand injectites in seismic data: implications for reservoir development. Issue 2 (2022) - Bradaric, Alma Dzozlic; Andersen, Trond; Lecomte, Isabelle; Løset, Helge; Eide, Christian Haug
No abstract available